Pemanfaatan Ikan Cakalang menjadi Abon di Rua Kota Ternate, Maluku Utara - Deniansyah Damanik; M. Dzaky Hilmy Lubis (Jurnal Abdi Mas Adzkia, 2020)
This community service aims to provide knowledge to the community about various fish management and good packaging methods to make it more modern, durable, and hygienic. The establishment of a Cakalang fish processing product center to become Shredded, increases the ability of business management in the community. While the methods used are counseling, practice, and discussion. The result of this program is the increasing ability of the community in managing fish into various processed, nutritious and high economic values, as well as evaluation efforts such as taste quality, marketing strategies, halal certification, and product permits. This program is a medium for sharing and changing the perspective of the community to jointly increase community empowerment to be prosperous and have a better income.